A New Paradigm in Vocabulary Instruction: AI-Based Language Learning Theory - Yusuf, Rusdi Muhammad (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The rapid development of artificial intelligence (AI) has profoundly reshaped the educational landscape, particularly in the area of vocabulary teaching for foreign language learners. This paper presents a new perspective on vocabulary instruction that integrates language learning theories with AI-driven technologies. Using a descriptive-qualitative method supported by a literature review of national and international journals published within the past decade, the study highlights AI’s potential to promote personalization, enhance learning efficiency, and increase interactivity. Tools such as chatbots powered by large language models (LLMs), mobile-based gamified platforms, and adaptive learning systems can provide content tailored to individual learners’ needs and profiles. However, several challenges remain, including inadequate infrastructure, insufficient teacher preparedness, ethical and privacy issues, and the risk of excessive dependence on AI. To address these issues, the study proposes strategies such as teacher professional development, strengthening digital literacy, and integrating AI into curricula in alignment with sound pedagogical principles. Ultimately, AI is envisioned not as a substitute for teachers but as a tool to support and empower them as facilitators of intelligent and engaging learning experiences. The successful implementation of AI-based vocabulary instruction depends on the synergy between technology, pedagogy, and local cultural values. The article concludes with practical recommendations for educators and learners to adapt to these technological shifts thoughtfully and critically, encouraging a more dynamic and transformative learning process.